Kekuatan Imajinasi Anne: Sebuah Studi Dalam Novel â€œAnne of Green Gablesâ€ - Dyah Utami Dewi; Febryano Manggala Putra (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study is conducted to analyze how Anne Shirley’s imagination helped her world in ''Anne of Green Gables''. Anne’s character is fascinating to analyze. Her concept of imagination and creativity can have practical implications for educators in mentoring students. It can help individuals to face challenges and improve mentally who may face difficult situations. The research method used was to combine qualitative and literary analysis. Collecting data by reading the book and noting the instances in which Anne uses her imagination, as well as the impact of her imagination on her life and those around her, to gather information. Analyzing the collected data by classifying the instances where Anne uses her imagination, finding patterns, and discovering themes. The moments show the power of imagination from Anne Shirley’s naming the avenue of trees, the Lake of Shining Waters, playing "Lady of Shallot, and pretending to be a famous opera singer. The events that are depicted in the book demonstrate to us that imagination is a potent tool that can assist us in overcoming difficulties, discovering happiness and beauty in life, and even creating our own realities.